Drying Time and Quality of EDS-Treated Compared to Untreated Beech Wood (Fagus japonica) - Mihaela CAMPEAN; Sachio ISHII; Sergiu GEORGESCU (Pro Ligno, 2017)
The paper presents the results of an experimental study performed with Japanese beech timber heattreated by the EDS method (Japanese patent) and then dried in order to evaluate the effects of this treatment upon the drying rate and the drying uniformity. The obtained results demonstrate benefitting effects of the EDS treatment both upon the drying time and the drying quality. The drying rate of EDS-treated beech wood is by 29% higher in the case of wood without red heart and by 11% higher in the case of wood with red heart. As far as the drying uniformity is concerned, the minimum moisture content gradient across the 50mm thickness of the timber boards was recorded for the EDS-treated beech wood with red heart (∆MC=1.66), by 21.7% lower than in the case of untreated beech wood with red heart.